Clinicopathologic Significance of HIF-1α, CXCR4, and VEGF Expression in Colon Cancer - Yugang Wu; Min Jin; Huanbai Xu; Zhang Shimin; Songbing He; Liang Wang; Yanyun Zhang (Clinical and Developmental Immunology)
We investigated the clinicopathologic significance of HIF-1, CXCR4, and VEGF expression using immumohistochemistry in human colon cancer. HIF-1, CXCR4, and VEGF high expression levels were correlated positively with TNM stage, lymph node involvement, and distant metastasis Furthermore, we found that combined high expression of any two of the three molecules (P=.028 for HIF-1/CXCR4, P=.007 for HIF-1/VEGF, and P=.004 for CXCR4/VEGF) had stronger correlation with lymph node metastasis than did each alone. However, a relationship with distant metastasis is seen only with the combinations CXCR4/VEGF (P=.069 for HIF-1/CXCR4, P=.062 for HIF-1/VEGF, and P=.035 for CXCR4/VEGF) as compared with those of single molecule high expression alone. Combined expression of all three molecules strongly correlates with lymph node metastasis and distant metastasis. The mRNA expression of HIF-1, CXCR4, and VEGF were quantified by real-time PCR in different colon cancer tissue samples, the experiment results shown that fresh colon tissue samples significantly overexpressed CXCR4 and VEGF mRNA compared with negative control. Therefore, the disease-free survival of all patients after curative resection can be considered in association with all three markers expression.